NPY Receptors Blockade Prevents Anticonvulsant Action of Ghrelin in the Hippocampus of Rat - Mina Ghahramanian Golzar; Shirin Babri; Zohre Ataie; Hadi Ebrahimi; Fariba Mirzaie; Gisou Mohaddes (Tabriz University of Medical Sciences, 2013)
Purpose: Ghrelin has been shown to have antiepileptic function. However, the underlying mechanisms by which, ghrelin exerts its antiepileptic effects are still unclear. In the present study, we investigated whether neuropeptide Y (NPY) mediates ghrelin anticonvulsant effect in the brain through its Y1, Y2 or Y5 receptors. Methods: Male Wistar rats were bilaterally microinjected with ghrelin 0.3 nmol/μl/side and NPY antagonists; GR231118 (Y1 receptor antagonist), BIIE0246 (Y2 receptor antagonist), CGP71683 (Y5 receptor antagonist) or solvents (Saline, DMSO) into the dorsal hippocampus 20 minutes before ghrelin administration. Thirty minutes after ghrelin microinjection, a single convulsive dose of pentylenetetrazole (PTZ) (50 mg/kg) was injected intraperitoneally (ip). Afterwards, duration of seizure and total seizure score (TSS) were assessed for 30 minutes in all animals. Results: Intrahippocampal injection of 0.3 nmol/μl/side ghrelin decreased duration of seizure and TSS induced by PTZ. The suppression of both duration (p< 0.001) and TSS (p< 0.001) induced by ghrelin in hippocampus were significantly blocked by GR231118 (10 μg/μl/side), BIIE0246 (400 pmol/μl/side) and CGP 71683A (5 nmol/μl/side). Conclusion: Our findings suggest that NPY Y1, Y2 and Y5 receptors in the hippocampus may somehow mediate the anticonvulsive action of ghrelin. Therefore, it is possible to speculate that ghrelin acts in the hippocampus to modulate seizures via NPY.